(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article examines and reflects the role and significance of crowdfunding platforms in the development of women’s human capital along with other financial resources, the role and significance of crowdfunding platforms in the development of women’s human capital, assesses the rationality (reasonableness) of using crowdfunding, provides an algorithm for presenting a project on a crowdfunding platform.